Model Development, Application and Optimization of Chlorination Breakpoint in Wastewater Treatment - Khawaga, Rehab Ibrahim (2017)
A Master of Science thesis in Chemical Engineering by Rehab Ibrahim Khawaga entitled, “Model Development, Application and Optimization of Chlorination Breakpoint in Wastewater Treatment”, submitted in December 2017. Thesis advisors are Dr. Sameer Al-Asheh and Dr. Nabil Abdel Jabber and thesis co-advisor is Dr. Mohamed Abouleish. Soft and hard copy available.